The resurgence of China’s third world policy in the 21st century - Alves, Ana Cristina (ISCSP, 2020)
Although the developing world has been a constant feature in Beijing’s foreign policy since the founding of the People’s Republic of China, it has never before assumed such overpowering proportions, evidenced by its unprecedented economic presence and influence in Africa, Asia and Latin America. A variety of factors contributed to this new reality, which impact in the global geopolitical landscape is yet to be fully understood. This article aims at analysing the factors behind the resurgence of the Third World in Chinese Foreign Policy in the 21st Century and discusses the ensuing strategic and political shifts in global governance.